Reporting on Vital Agricultural News in Ireland – a Comparison between Mainstream Print Media and the Farming Press - Claire Mc Cormack; Pádraig Wims (Journal of Applied Communications, 2022)
The purpose of this paper is to compare the reporting of vital agricultural news between the mainstream print media and the farming press in Ireland. To achieve this, this study examined coverage of a recent and significant agricultural news event by mainstream Irish newspapers and the Irish farming press. Taking the 2018–2019 Irish beef sector crisis as the case study for examination, researchers conducted a comparative content analysis of the most widely circulated mainstream national newspapers’ (n = 5) and farming newspapers’ (n = 2) coverage of the story over a 14-month period. We analyzed the timing, frequency, and placing of some 294 articles published to communicate issues regarding the beef crisis at three specific stages—before the national farmer protests, during the farmer protests, and after the farmer protests. We found mainstream newspapers to be significantly slower to start reporting on the Irish beef sector crisis of 2018–2019 compared to the country’s farming newspapers—although national print media coverage of the event increased as the crisis escalated. This early underreporting of the event by mainstream newspapers is compelling considering the importance of the agri-food sector, and beef farming in particular, to Ireland’s economy. Building on existing international, but very limited Irish, research on agricultural journalism, we concluded that farming newspapers are more in touch with the critical issues affecting Irish farmers while mainstream newspapers appeared slower to cover a vital agricultural issue of public importance.
Keywords: mainstream media; agricultural media; content analysis; print media; beef plan movement; specialized journalism